Behavior of Lightweight Aggregate Concrete with FRP Confinement: Experimental Insights for Structural Applications - Butje Alfonsius Louk Fanggi; Yuyun Tajunnisa; Hazen Masrafat; Jusuf Wilson Meynerd Rafael; Alva Yuventus Lukas; Niakku Immanuel Maggang; Joko Suparmanto; Melati Tabita Kirana Thei (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
Lightweight aggregate concrete reduces structural dead load but generally exhibits lower compressive strength and ductility than normal-weight concrete. This study experimentally evaluates the effectiveness of carbon-fibre-reinforced polymer (CFRP) confinement for low-density lightweight aggregate concrete, an area in which data for square sections remain limited. Twelve 300-mm-high specimens with a density of approximately 1550 kg/m³ were tested under monotonic concentric compression. The investigated parameters were concrete compressive strength (15 and 28 MPa), cross-sectional shape (square and circular), and number of CFRP layers (one and two). Failure occurred through localized, extensive, or hoop rupture of the CFRP. The confined specimens exhibited approximately bilinear stress–strain responses and substantial improvements in strength and deformation capacity. For square specimens with 15 MPa concrete, two CFRP layers increased the average strength ratio to 2.27 and the strain ratio to 23.39. Circular specimens developed greater confinement efficiency, reaching an average strength ratio of 3.76 with two layers. Lower-strength concrete showed larger relative ductility gains than higher-strength concrete. These findings demonstrate that CFRP confinement can substantially reduce the brittle response of low-density lightweight concrete and support its use in lightweight, resilient, and earthquake-resistant structural applications.